2008
DOI: 10.1002/pd.1920
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking autonomy in the context of prenatal screening decision‐making

Abstract: The active offer of an unsolicited prenatal test need not be considered as an impediment for making an autonomous choice. The moral significance of prenatal testing is inseparably bound with the social context in which it is practiced. Influence from other persons and emotional reactions due to the test offer can be interpreted as supportive for making a choice. In clinical practice, testing should be timely offered in order to give women the opportunity of discussing their views with significant others. Careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 35 publications
5
46
0
1
Order By: Relevance
“…Earlier studies have shown that many women want to share the decisionmaking about prenatal screening with their partners [44] and as Garcia et al point out, the partner therefore also needs to be well informed about the purpose of ultrasound scan [2,44].…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…Earlier studies have shown that many women want to share the decisionmaking about prenatal screening with their partners [44] and as Garcia et al point out, the partner therefore also needs to be well informed about the purpose of ultrasound scan [2,44].…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…Although partners may provide support during this period, it's also possible that they contribute to conflict and uncertainty (Humphreys et al, 2008). Avoiding marital conflict can even lead women to follow their partners' opinion when couples disagree on whether or not to have IDTs (García, Timmermans, & van Leeuwen, 2008). Consistently, couple's level of agreement regarding IDTs before the first appointment predicted marital adjustment after receiving the results (Humphreys et al, 2008).…”
Section: Couples' Decision-making Regarding Amniocentesismentioning
confidence: 54%
“…Research by García et al (2008) indicate however, that women do not want to shoulder all the responsibility for the decision about prenatal testing. Moreover, they suggest that making joint decisions would help women to feel more comfortable about their final choice and that professionals should, therefore, support women to discuss testing with their significant others.…”
Section: The Decision Concerning Amniocentesis or Notmentioning
confidence: 92%